Over honderd ziekten - Jacob Ruiter, Dirk (Radboud University Press, 2023)
This book offers exciting and often surprising insights into one hundred diseases that have emerged over the past century. The authors focus on the period from 1923, when Radboud University was founded, to 2023, the university's centennial anniversary. All of the diseases included in this book have left an indelible mark on the century in which they emerged, in either a scientific and/or socio-historic sense. This book can therefore be read as a series of descriptions of time-specific degenerative disorders, inflammations, infections, malignant neoplasms, immunological diseases, developmental disorders, genetic diseases and psychiatric disorders. All of the descriptions are accompanied by vivid illustrations, the majority of which come from the Museum of Anatomy and Pathology at Radboud university medical center. Each disease description also includes a critical commentary and a brief historical framework. Scientific findings by Dutch and Nijmegen researchers are highlighted, where applicable. Finally, each disease description also includes an English summary. The book A Century of Diseases is accessible to a wide audience of readers with an interest in pathology, ranging from students and staff at Radboud University and Radboud university medical center to those involved in all facets of healthcare, from professionals to patients.